2023
DOI: 10.3390/su15043328
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Behaviours of Young Consumers towards Wasting Food: Case Study Based on Polish Students

Abstract: Civilisation changes affect the attitudes and behaviour of consumers related to food waste. Most food is wasted by households. The purpose of this study was to assess the behaviour and attitudes of Polish students related to food waste and to determine the amount and type of food waste, as well as to indicate the causes of this problem. The analysis of attitudes and behaviours of individual groups of society directs actions to be taken in order to reduce food waste. For 14 days, a questionnaire was completed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Extending the shelf life (delaying staling) of bread seems to be important for reducing food waste. According to respondents, the most frequently thrown-away products included fruit and vegetables, followed by bread [13,14]. Reducing the problem of food waste should lead to decisive actions aimed at educating consumers according to the idea of "Don't waste food", because bread and bakery products account for more than 50% of total food waste [69].…”
Section: Characteristics Of Technological Properties and Color Parame...mentioning
confidence: 99%
See 1 more Smart Citation
“…Extending the shelf life (delaying staling) of bread seems to be important for reducing food waste. According to respondents, the most frequently thrown-away products included fruit and vegetables, followed by bread [13,14]. Reducing the problem of food waste should lead to decisive actions aimed at educating consumers according to the idea of "Don't waste food", because bread and bakery products account for more than 50% of total food waste [69].…”
Section: Characteristics Of Technological Properties and Color Parame...mentioning
confidence: 99%
“…Najafabadi et al [12] showed that baking and storage conditions of bread influence staling. The staling of bread is one of the reasons for throwing it away, and food waste is a common problem in many societies [13,14]. The demand for bread with good technological, sensory, and functional values, as well as extended shelf life, causes producers to look for various components, especially natural ones, to meet the growing expectations of consumers.…”
Section: Introductionmentioning
confidence: 99%
“…The government increases awareness about food waste through educational practices (Pinto et al, 2018) because food waste increases due to consumers' low knowledge and ability to manage food (Graham-Rowe et al, 2015;Werf et al, 2020). Meanwhile, food businesses can significantly reduce food waste by offering products with various portion options, accompanied by date labels and retail marketing (Tarczyńska et al, 2023).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%